1991
DOI: 10.1007/bf02470866
|View full text |Cite
|
Sign up to set email alerts
|

A simple experimental model of total hepatectomy, hepatic ischemia and extrahepatic portal obstruction in rats using splenic transposition

Abstract: The objective of this study was to develop an easy and simple experimental rat model of total hepatectomy, hepatic ischemia and extrahepatic portal obstruction. The first operation involved transposing the spleen with its scarified capsule in a subcutaneous pouch to produce portasystemic anastomosis. Total hepatectomy was easily performed in a lobe-by-lobe fashion 2 weeks following the first stage operation. Anhepatic rats receiving a glucose infusion survived for about 10 hours and all died of acute hepatic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A second model involves PSS induced by subcutaneous transposition of the spleen [11]. This model also has been reported to be easy to create [11,28]. Since portosystemic collaterals are formed within 3 weeks after subcutaneous transposition of the spleen in rats, it takes about 3 weeks to perform the experiment.…”
Section: Figmentioning
confidence: 98%
“…A second model involves PSS induced by subcutaneous transposition of the spleen [11]. This model also has been reported to be easy to create [11,28]. Since portosystemic collaterals are formed within 3 weeks after subcutaneous transposition of the spleen in rats, it takes about 3 weeks to perform the experiment.…”
Section: Figmentioning
confidence: 98%
“…Total Hepatic Ischemia. To minimize splanchnic congestion during total hepatic ischemia, we performed subcutaneous transposition of the spleen with its scarified capsule to induce development of portosystemic collaterals between the spleen and the anterior abdominal wall, as described by Omokawa et al (20). Four weeks later, after the establishment of adequate portosystemic collaterals, the animals were subjected to total hepatic ischemia.…”
Section: Animals Male Wistar Rats Each Weighing About 200 Gmmentioning
confidence: 99%
“…The studies about the potential effectiveness of the portosystemic shunt on hepatic I/R injury have focused mainly on normothermic conditions (3,(11)(12)(13)(14)(15). In this regard, the portosystemic shunt leads to increased survival (12,13), extended times of sustained ischemia (3,11), and reduced levels of plasma TNF after hepatic I/R in experimental models of total normothermic ischemia (3). However, few studies (16 -18) have reported on the benefits of the portosystemic shunt in cold ischemia associated with rat liver transplantation.…”
mentioning
confidence: 99%